QRIS Adoption by MSMEs in the UTAUT Perspective - wahyuningsih, wahyuningsih; Avrianto, Alam (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
Abstract– In Indonesia, QRIS is presently a payment system that is gaining popularity. However, there are still a number of obstacles in the way of MSMEs using QRIS as a payment method. The purpose of this study is to use the UTAUT and TAM constructs to more thoroughly investigate the factors that influence MSMEs in the Garut Regency to adopt QRIS. Utilising a quantitative methodology, this investigation. The variables in this research consist of Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), User Attitude (UA), adoption of QRIS (Adopt), and Financial Literacy (FL). The research results show that the factors that encourage increased financial literacy in MSMEs include Performance Expectancy, Social Influence, and User Attitude. Meanwhile, the factors that encourage the adoption of QRIS by MSMEs are Social Influence, User Attitude, and Financial Literacy.